2015
DOI: 10.3988/jcn.2015.11.3.234
|View full text |Cite
|
Sign up to set email alerts
|

On the Severity of Carpal Tunnel Syndrome: Diabetes or Metabolic Syndrome

Abstract: Background and PurposeCarpal tunnel syndrome (CTS) is the most common entrapment neuropathy. Although its etiology is unknown, certain conditions are commonly associated with CTS, such as obesity, arthritis, hypothyroidism, diabetes mellitus, trauma, mass lesions, amyloidosis, and sarcoidosis. We aimed to determine the association between metabolic syndrome and CTS, and we compared the severity of CTS between patients with diabetes (and no concomitant metabolic syndrome) and patients with metabolic syndrome.Me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

3
27
1
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 29 publications
(34 citation statements)
references
References 22 publications
3
27
1
1
Order By: Relevance
“…The CTS incidence peaks at a mean age of 40-60 years. [3] In a study by Yurdakul et al, [2] the mean age was 46.3±12.2 years, and 85.7% of the patients were female. Similarly, in the current study, CTS was observed 75.6% in females; however, the mean age of our patients was higher than the prior study (52.0±8.2 years) and its lead to high recurrence rate for the one reason.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The CTS incidence peaks at a mean age of 40-60 years. [3] In a study by Yurdakul et al, [2] the mean age was 46.3±12.2 years, and 85.7% of the patients were female. Similarly, in the current study, CTS was observed 75.6% in females; however, the mean age of our patients was higher than the prior study (52.0±8.2 years) and its lead to high recurrence rate for the one reason.…”
Section: Discussionmentioning
confidence: 99%
“…[1] Although the etiology of CTS is not fully known, risk factors, such as repetitive use of the wrist, advanced age, obesity, pregnancy, acromegaly, trauma, amyloidosis, diabetes mellitus (DM), kidney disease, thyroid disease and osteoarthritis were reported to be responsible. [2] Carpal tunnel syndrome is most frequently observed in the age range of 40 to 74 years, and the general prevalence in the population is 2.7 to 5.8%. [3] However, CTS is observed at rates that are 10-fold higher in females than in males.…”
mentioning
confidence: 99%
See 3 more Smart Citations